(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To report the prevalence of and describe symptoms of PLP and RLP in children and adolescents who have undergone upper and lower limb amputation. Study Design: Cross-sectional study Methods: This study was carried out at Children’s Hospital, Lahore from June 2024 to January 2025. Convenience sampling was used to include 245 children and adolescents (6-16 years old) with major limb amputation (at least 6 months after amputation). The Short-Form McGill Pain Questionnaire (SF-MPQ-2) and a demography proforma were used to gather data. The Numeric Rating Scale (children aged 8-16 years) and Faces Pain Scale-Revised (children aged 6-7 years) were used to rate pain intensity. Data were analysed using SPSS (v 26.0). Results: The overall prevalence of PLP was 52.2% (n=128) and RLP was 40.0% (n=98). PLP prevalence increased significantly with age: 41.0% in children aged 6-9 years, 54.1% in children aged 10-12 years, and 63.4% in adolescents aged 13-16 years (χ² = 12.74, p = 0.002). There was no age association for RLP (p = 0.229). RLP did not significantly increase with age (p = 0.229). Aching (17.1%), tingling (16.7%) and throbbing (14.7%) were the most frequent pain descriptors. Pain interfered with mood (68%), sleep (55%) and school (34%). Conclusion: PLP and RLP are commonly reported in children with amputations, with a striking increase in PLP with increasing age. These data require systematic pain assessment and treatment of all children with amputation, taking into account their developmental stage.